2009
DOI: 10.1098/rsta.2008.0262
|View full text |Cite
|
Sign up to set email alerts
|

Tristable electrical conductivity switching in a polyfluorene–diphenylpyridine copolymer with pendant carbazole groups

Abstract: Tristable electrical conductivity switching and non-volatile memory effects are demonstrated in a conjugated copolymer of poly(2,6-diphenyl-4-((9-ethyl)-9H -carbazole)-pyridinyl-alt-2,7-(9,9-didodecyl)-9H -fluorenyl) (PPCzPF). The indium-tin oxide (ITO)/PPCzPF/Al device can be switched from the low-conductivity (off) state to the first high-conductivity (on-1) state at 1.8 V, with an on/off current ratio of approximately 100. The device can be further switched from the on-1 state to the next higher conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Interestingly, a tristable electrical conductivity switching memory effect was observed for a conjugated copolymer of poly(2,6‐diphenyl‐4‐((9‐ethyl)‐9 H ‐carbazole)‐pyridinyl‐alt‐2,7‐(9,9‐didodecyl)‐9 H ‐fluorenyl) ( P27 , Scheme ) . The ITO/ P27 /Al device can be switched from the low‐conductivity state to the first high‐conductivity (ON‐1) state at 1.8 V, with an ON/OFF current ratio of approximately 100.…”
Section: Functional Polymers For Non‐volatile Memory Devicesmentioning
confidence: 99%
“…Interestingly, a tristable electrical conductivity switching memory effect was observed for a conjugated copolymer of poly(2,6‐diphenyl‐4‐((9‐ethyl)‐9 H ‐carbazole)‐pyridinyl‐alt‐2,7‐(9,9‐didodecyl)‐9 H ‐fluorenyl) ( P27 , Scheme ) . The ITO/ P27 /Al device can be switched from the low‐conductivity state to the first high‐conductivity (ON‐1) state at 1.8 V, with an ON/OFF current ratio of approximately 100.…”
Section: Functional Polymers For Non‐volatile Memory Devicesmentioning
confidence: 99%
“…[1e, h, 2] To meet the demands for high-density datas torage (HDDS), one strategyu nder consideration is the realization of multilevel (e.g.,t ernary) memory devices, which can increase the data storagecapacity from 2 n to 3 n . [3] Recently,Kang et al [4] reported ap olymer-based ternary memory device that operated throught wo mechanisms. However,t ernary memory performance is limited to nonvolatile memory,w hich makes it difficult to face the practical demand for varioust ernary memory types.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the demands for high‐density data storage (HDDS), one strategy under consideration is the realization of multilevel (e.g., ternary) memory devices, which can increase the data storage capacity from 2 n to 3 n . Recently, Kang et al . reported a polymer‐based ternary memory device that operated through two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the solution processing capability of organic materials allows them to be handled via dip coating, blade casting, spray coating, spin coating, rollercoating and even ink-jet printing, not only making the more elaborated processes of vacuum deposition of functional thin films eliminable, but allowing the fabrication of flexible memory chips. Extensive studies have been performed on the resistance switching in organic materials, wherein focus has been concentrated on the development of novel materials for memory performance [28][29][30][31][32][33][34][35] optimization.…”
Section: Resistive Switching Mechanisms In Organic Materialsmentioning
confidence: 99%